Strategies for learning English in higher education: a systematic mapping - Saez-Zevallos, Nataly Susan; Montalvo-Apolín, Danitza Elfi (Frontiers in Education, 2025)
The prevalence of English in higher education has necessitated its learning and mastery, both for the internationalization of the language across countries and for its utility as a crucial tool in scientific and educational interactions. Consequently, this study aimed to identify and characterize scientific articles published between 2020 and 2024, focusing on metacognitive, cognitive, socio-emotional, and technological strategies in the learning of English among university students. This was achieved through a qualitative systematic mapping using databases such as Scopus, ERIC, EBSCO, and Web of Science. The methodology, with a qualitative orientation, incorporated the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) processes, encompassing three moments: (1) Search approach, (2) Development of the search protocol, and (3) Analysis of results and classification and synthesis process. A total of 80 articles were selected based on quality, inclusion, and exclusion criteria. The findings indicated that China and the United States have the highest number of studies; the most cited author has 32 citations; methodological perspectives include quantitative, mixed, and qualitative approaches; and the questionnaire was the most frequently used instrument. The journals of interest span all four quartiles. Notable technological strategies include augmented reality, artificial intelligence, and the metaverse, while metacognitive and cognitive strategies such as self-regulated learning are emphasized. Research lines highlight the interactivity and effectiveness of pragmatic strategies in English feedback and trends in identifying factors that cause anxiety during English classes. It is concluded that English is instrumental in enhancing article writing strategies and scientific dialogue in English. It is recommended to implement strategies to develop the competence of writing scientific articles in English and to utilize educational platforms for learning scientific and communicative English.